A PROPOSED DESIGN OF INTEGRATED PERFORMANCE MANAGEMENT SYSTEMS FOR MANAGING CONFLICTING OBJECTIVES AND ALIGNING PERFORMANCE OF TRANSPORT LOGISTICS - Prama Irfani, Dian
Companies with multiple roles, as a profit generator and public service provider, have specific characteristics that are different from single-role companies. However, literature suggests that no Performance Management System (PMS) framework exists to fully suit the characteristics of such companies. This study aims to develop a novel PMS framework to manage transport logistics performance in multiple-role companies.